EMPLOYMENT BASED ON A FICTION: EVALUATING THE LEGITIMACY OF TRADITIONAL NOTIONS OF CONTRACT IN THEIR APPLICATION TO AN ATYPICAL EMPLOYMENT RELATIONSHIP - Andre M Louw (Obiter, 2022)
This article will examine the employment relationship between players in professional team sports and their employers. It will focus briefly on the nature of this relationship and on some unique characteristics that serve to distinguish this relationship from the employment of other employees. The author argues that the general view that the employment contract is largely based on a fiction (in respect of the respective parties’ bargaining power and freedom to contract) is of special importance in professional sport. As the traditional checks and balances which serve to assuage the employer’s significant power are mostly absent in this context, and one encounters an additional factor that serves to further limit the rights and freedom of the player-employee (namely the degree to which the rules and regulatory conduct of sports governing bodies, and especially international sports governing bodies, form part of the employment relationship and are incorporated in the terms and conditions of employment), it will be argued that this fictional nature of the employment contract is especially relevant. It will further be argued that the courts’ traditional view of the nature of sports governing bodies and of the basis for their authority over participants (including professional player-employees) needs to be reviewed. In light of this the author will argue that the construct of a contract cannot legitimately serve as basis for the incorporation of the rules and regulatory conduct of international sports governing bodies in the employment of players in the domestic context (also in light of constitutional freedoms and fundamental rights of employees), and that an alternative basis for the position of authority of such bodies in this context must be found. A future paper will continue this evaluation, with reference to the possible role of international law.